Sino-Nasal and Olfactory System Disorders - Heinbockel, Thomas; Singh Gendeh, Balwant (IntechOpen, 2020)
Our sense of smell is of critical importance in our daily lives and it contributes to our personal wellbeing and safety as well as communication with others. However, it is only when disease or injury impairs its function that we appreciate the relevance of this sensory modality. During the past three decades, research of the olfactory sense has seen an ever-growing interest in this exciting field of study. This book provides the reader with an overview of the latest developments in sino-nasal and olfactory system disorders and focuses on the most important evidence-based developments in this area. This book addresses disorders, dysfunctions, diseases, and syndromes of the olfactory system ranging from molecular, cellular, and systems to cognitive and behavioral topics. Individual chapters center around recent advances in specific areas of chemosensory pathological conditions, while other chapters focus on technological developments to study the function and dysfunction of the olfactory pathways.